Implementasi pendekatan pendidikan matematika realistik ditinjau dari pemahaman konsep, aktivitas, dan respons siswa - Marzuki Ahmad; Dwi Putria Nasution; Sabri Sabri (Journal of Didactic Mathematics, 2021)
This study aims to describe the ability to understand mathematical concepts, activities and student responses in learning mathematics with realistic mathematics education approach. To achieve this goal, a quasi-experimental study was conducted with one group pretest posttest design. The population of the study was the eighth grade students of SMP Negeri 4 Angkola Timur, sampling by purposive sampling, namely class 8-2, totaling 26 students. Research activities include the stages of giving the Pre-test followed by learning for 3 meetings which then ends with a final test. Through research conducted using the Paired Samples Test, a significance of 0.00 < 0.05 was obtained, which gave the decision that the initial hypothesis was accepted. Of the 9 aspects of learning activities studied in the application of realistic mathematics education, the overall average value of the percentage of all activities met the active criteria. Furthermore, the average overall student response to being happy, new, interested and understanding/interested in the implementation of realistic mathematics education is 91.11% ≥ 85%. Thus it is concluded that: 1) The implementation of a realistic mathematics education approach has a significant positive influence in learning students' ability to understand mathematical concepts; 2) Student activities in learning mathematics with realistic mathematics education approach are effective; 3) Student responses to learning activities with realistic mathematics education are in the positive category.